TeamPlus: A Decision Support System for Software Team Formation - Cunha, Felipe; Perkusich, Mirko; Almeida, Hyggo; Gorgônio, Kyller; Perkusich, Angelo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The literature presents several search and optimization-based solutions for the software team formation problem. However, the existing solutions do not reflect the real needs of practitioners. In general, they do not systematically address the problem, provide adequate visual resources, or integrate with data from enterprise systems. Therefore, the existing solutions are unaware of the actual dynamics of projects and miss important historical information from team members. This paper introduces TeamPlus, a Decision Support System capable of communicating with the people management environment and applying quantitative measures to data to build profiles, suggest teams based on entry criteria and allow the manager to manipulate the suggestions and adjust the preferences before the best decision is made. We developed TeamPlus through a qualitative study with industry practitioners and validated it, given its practical utility and effectiveness. This paper presents an overview of its main features, a comparison with other existing solutions, and preliminary evaluation results. Link to video: https://youtu.be/Uhf_aYCjh9o License type: Proprietary software (no public license)